Pharmacological correction of periodontitis using synthetic analogues of indolicidin - Igor V. Kutepov; Yuri D. Lyashev (Belgorod National Research University, 2019)
Introduction: The leading role of pathogenic microorganisms in the pathogenesis of periodontitis is beyond doubt. However, the use of antibiotics for periodontitis is associated with a number of problems. Indolicidins have a unique anti-microbial effect. The relevance of the search for new drugs for the treatment of acute periodontitis based on the natural indolicidin peptide becomes obvious. Materials and methods: The investigation was performed on 320 Wistar male rats, using synthetic analogues of natural indolicidin: No. 7 and No. 8, which were administered intraperitoneally at a dose of 500 µg/kg in a volume of 0.2 ml once a day for 7 days. Periodontitis was simulated in animals according to the method proposed by Volozhin A.I. and Vinogradova S.I. Results and discussion: The correcting effect of indolicidin analogues on the periodontitis course, was manifested by a decrease in edema and in the relative area of cell infiltrates, a significant increase in the relative area of normal tissue, and a correction of the periodontal composition. The use of indolicidin analogues led to an increase in the functional activity of neutrophils and macrophages, acute phase proteins concentration, a correction of pro-oxidant-antioxidant balance and production of vasoactive substances. The effect of indolicidin analogues was higher than that of lincomycin. The greater effectiveness of peptide No.8 compared to that of No.7 was established. Conclusion: The investigation opens up the prospects of the synthesis of new antimicrobial drugs on the basis of the synthetic analogues of indolicidin.